Attending to migrant health in Scotland’s Ending HIV policy - Chase Ledin (Critical Public Health, 2025)
This study examines the role of migration in Scotland’s policy to end new HIV transmissions by 2030. Migration is defined as a key social determinant of HIV treatment and prevention in global health scholarship. However, critical understandings of migration and HIV transmission are uniquely under-explored in the Scottish policy context. Previous scholars have articulated the need for intersectional approaches to developing relevant policy measures for migrant communities impacted by HIV transmission. Attending to the intersection of HIV and migration, this study uses document analysis of the Scottish Government’s Ending HIV policy (2024) to demonstrate how migration is absented from Scottish policy priorities. This study explores the consequences of omitting consideration of health inequalities for temporary and permanent migrants. The study finds that increases in migration patterns across Scotland shape the ‘missing’ population of people living with undiagnosed and/or untreated HIV, which must be acknowledged and included in the policy vision. This study argues for further intersectional approaches to integrate migrant experiences into Scotland’s health policy to end new HIV transmissions by 2030, including more targeted culturally sensitive health promotion practices and consultation with migrant communities from across Scotland.